High-temperature 3D printing of polyetheretherketone products: Perspective on industrial manufacturing applications of super engineering plastics. (1st December 2021) - Park, Seong Je; Lee, Ji Eun; Park, Jiyong; Lee, Nak-Kyu; Son, Yong; Park, Suk-Hee
Graphical abstract: Highlights: High-performance super engineering plastic of PEEK in 3D printing process. Highly optimized 3D printing system equipped with high temperature extruder and build chamber. Manufacturing of the structurally stable and mechanically reinforced constructs. Achievement of a high degree of crystallinity and tensile strength. Demonstration of the suitability of 3D printed PEEK structures for industrial applications. Abstract: A refined additive manufacturing system of material extrusion type was developed considering the high-temperature conditions of extruder and chamber. With this setup, a super engineering plastic material, named polyetheretherketone (PEEK), could be printed into three-dimensional (3D) parts without any delamination or warpage. To obtain maximum performance in terms of mechanical strength, experimental studies were conducted considering the thermal process parameters such as nozzle and chamber temperatures. These optimal process settings and carefully controlled heating conditions, incorporated with post-processing of additional heat treatment, could provide a high degree of crystallinity and high tensile strength (i.e., more than 90% compared to original material properties). To demonstrate the feasibility of industrial applications, we fabricated and tested several product prototypes, such as a wafer jig, a lathe chuck part, and plastic injection molds, all of which confirmed the excellent performance of PEEK for chemical resistance, high strength, and heat resistance, respectively.